Physical and physiological changes in donkeys during pack load - PAL, YASH; GUPTA, A K; KUMAR, S (The Indian Journal of Animal Sciences, 2012)
Draughtability studies were carried out with adult, healthy and trained donkeys under 2 different work schemes i.e. continuous work and work-rest-work scheme with 2 different sets of loads (load equal to 40 and 50 % of their body weights). To assess their capability and work stress on them, physical observations, viz. unwillingness to continue operation, legs coordination, frothing, excitement, tongue protrusion etc. and physiological observations (rectal temperature, pulse rate, respiration rate) were recorded at fixed intervals. Under pack load equivalent to 40% of their body weight, donkeys worked for 4 h and 5 h under continuous as well as under work-rest-work cycle, respectively, while with 50% pack load, donkeys worked for 4 h under both work plans. After using standard fatigue score analysis technique, it was observed that donkeys attained a fatigue score of 6 and 4 out of 16 under continuous and work-rest- work cycle, respectively, for 40% as pack load while the fatigue score of 10 and 2 was observed under continuous and work-rest-work cycles, respectively, for 50% pack load. Intermittent rest in between work reduced the stress on these animals and resulted in increasing the work periods.